2022
DOI: 10.1177/15248380221090980
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Global Definition and Understanding of Child Sexual Exploitation: The Development of a Conceptual Model

Abstract: Child sexual exploitation (CSE) is a serious and persistent global issue affecting up to 5% of the child and youth population worldwide; yet there is no universally accepted definition. To develop a theoretically robust definition of CSE, this review systematically synthesized literature examining CSE definitions aiming to develop a conceptual model and typology. Electronic databases were searched to February 2021, yielding 384 nonduplicative records. Inclusion criteria were peer-reviewed and grey literature i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 91 publications
0
14
0
1
Order By: Relevance
“…The stimulant effect of khat chewing exposes children to feelings of sexual activity such as watching pornographic movies, which make them to easily manipulated by perpetrators [ 47 ]. Evidence indicated that perpetrators of sexual abuse usually use substances such as alcohol, chat, and cigarette as tool to take advantage of someone who is vulnerable and lacking capacity for decision making [ 48 , 49 ]. In this review, gender is identified as determinants of child sexual abuse.…”
Section: Discussionmentioning
confidence: 99%
“…The stimulant effect of khat chewing exposes children to feelings of sexual activity such as watching pornographic movies, which make them to easily manipulated by perpetrators [ 47 ]. Evidence indicated that perpetrators of sexual abuse usually use substances such as alcohol, chat, and cigarette as tool to take advantage of someone who is vulnerable and lacking capacity for decision making [ 48 , 49 ]. In this review, gender is identified as determinants of child sexual abuse.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of children, the definition also includes procurement or grooming, SA, adverse sexual experiences, child sexual victimisation, and sexual exploitation (Mathews & Collin‐Vézina, 2019). Sexual exploitation is considered to be any act of abuse or attempted abuse in exploitive relationships where the survivor is in a position of vulnerability and the perpetrator has power over the survivor, and can include transactional/solicitation of sex in exchange for money, or other forms of remuneration such as social or political gain (Laird et al., 2022). Sexual harassment includes unwanted physical contact, sexual invitations, sex‐based taunts, insults, comments or innuendo, and exposure to pornographic material (Saunders & Easteal Am, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For this review, the term CSEA incorporates child sexual abuse, that is, a harmful act occurring: (a) within a relationship of power, (b) where the young person holds a position of inequality and whose vulnerability is exploited, and (c) without true consent (Laird et al, 2022). Child sexual exploitation, according to a recent systematic review of 66 studies, is defined as:…”
Section: The Scale and Nature Of Csea In The Ukmentioning
confidence: 99%